Development of an Infant's Peripheral Motor System Within the First 3 Years of Life as Studied Using Surface Electromyography - Yu. R. Zaripova; A. Yu. Meigal; V. I. Makarova (Union of pediatricians of Russia, 2015)
The clinical assessment of the motor system's condition of a growing infant is often complicated due to the volatility of neurological symptoms.Aim. The study was aimed to follow the ontogenesis of the motor function from the 33rd week of postconceptual life to the 36th week of postnatal life using linear and nonlinear parameters of the surface electromyography (sEMG).Methods. The study was longitudinal by its design, selective, stratified and randomized. Premature (31/32 week of gestation) and term (38/39 weeks of gestation) infants were studied. Stratified by gestational and postnatal age, sex and neurological status.Results. In the premature infants the sEMG had an appearance of that of the first day term newborn seen as «simplified pattern», low amplitude and spectral frequency. The temporal dynamics of sEMG parameters were slower in premature infants. In contrast, a fast increase of nonlinear sEMG parameters in term newborns within the first year of life may be an evidence for a complication of the sEMG signal. The linear sEMG parameters increased monotonously across the first life year. Maximal values of both linear and nonlinear parameters were characteristic for the 6th month of life. That might reflect the critical period of formation of the cortico-spinal pathways and manipulative motion.Conclusion. The findings suggest the importance of the first two weeks of life in the development of musculoskeletal term infants, which is formed during the «adult» type of the motoneuron pool organization. At the same time, quantitative changes in sEMG (increase of amplitude) continued during all 36 months of the study, which indicates a continuing growth of skeletal muscles. sEMG in preterm infants features a more simple temporal organization. This suggests the continuing «intrauterine» pattern of the motor neuron pool work.